Practitioners' use of life cycle costing with environmental costs-a Swedish study. - Hochschorner, Elisabeth
Purpose The aim of this paper is to describe life cycle costing (LCC) practices in some Swedish organisations, investigate probable changes and determine whether and how environmental costs (internal and/or external) are considered in current LCC. Methods This paper is based on interviews with LCC practitioners working in authorities and companies in Sweden, mainly the Swedish defence sector, but also other sectors to broaden the study. Results and discussion. Those interviewees who use LCC all employ their own particular method, adjusted from case to case. Inclusion of future costs and use of interest rate is also decided from case to case. Conclusions The inclusion of direct, indirect, contingent and intangible costs differs between organisations. Even when environmental costs are considered in the LCC, not all the internal (environmental) costs are included. All interviewees believe that LCC can be important for decision making and most also believe that environmental costs, like other costs, influence final decisions, but still LCC is not always performed or used. The companies represented are large, and a particular individual cannot have insights into all methods or procedures used in different departments. The results are thus based upon interviews with individuals representing the companies and the responses might have been different if different individuals had been interviewed. However, since the answers between the different time periods and between the organisations point in the same direction, we found no need to make further interviews.
Keywords: Environmental costs; LCC; Life cycle costing; Practitioner use